Upravljanje znanja znotraj učnih okolij - Pivec, Maja (Uporabna informatika (Ljubljana), 1999)
The paper gives an analysis of the electronic library and the knowledge pool. Electronic library as enrichment of the electronic learning environment is comparable with the idea of the knowledge pool. In the paper usage of both systems is described with the emphasis on the knowledge re-use. Introduction of additional features opens new dimensions of the learning process within theelectronic lesrning environment. The ability of explanation of complex processes enables the usage of the technology as a cognitive tool that improves the comprehension. Development trends and usage of the technology for learning and knowledge management are presented.
Keywords: elektronski mediji; permanentno izobraževanje; upravljanje; znanje